Heavy Metals Toxicity in Selected Vegetables and Soil from Akpajo, Eleme Local Government, Rivers State - Nyimone, Paul D.; Anacletus, Francis C.; Patrick-Iwuanyanwu, Kingsley C. (European Journal of Applied Sciences, 2023)
Threat to life from anthropogenic contamination of soil and food crops harvested from our environment is now of immense public health concern. This study investigated heavy metals’ contentment in selected vegetables and soil water from Akpajo, in Eleme Local Government Area of Rivers State and probable toxicity effects on exposure to these food crops. Vegetables (Telfairia occidentalis (pimpkin leaf) and Vernonia amygdalina (Bitter leaf) and Soil from an agricultural farm land were collected and analyzed for Lead (Pb), Cadmium (Cd), Nickel (Ni), Arsenic (As) and Mercury (Hg) contents using Atomic Absorption Spectrophotometer (model: S4=71096). The maximum mean levels (mgkg-1) obtained for Pb 5.392±0.001and Cd (0.396±0.001mg/kg) were seen in V. amygdalina with minimum Pb (3.35±0.029mg/kg) and Cd (0.288±0.001mg/kg) seen in the soil and Telfairia occidentalis, (Pumpkin Leaf) samples respectively. Maximum Ni value (1.99±0.00mg/kg) was obtained from the sampled soil with the minimum value (1.108±0.001mg/kg) seen in Telfairia occidentalis. Arsenic and Hg were shown to be below detectable limits. Chronic Daily Intake (CDI), Target Hazard Quotients (THQ) and TLCR were used for heavy metals health risk assessment (HRA), which gave values higher than standard as stipulated by USEPA. These toxicological indices revealed that adult and children population exposed to these samples could be highly at risk as values obtained where above potential risk-free limit of 10-6 to 10-4 set by USEPA. It is however recommended that strict measures be developed and adopted to restrict further pollution of surrounding agricultural soil.